(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The article presents the behaviour of a structure subjected to fire - fire design situa- tion. A portal industrial hall with a span of 18.0 m, a length of 42.0 m and a column height of 7.0 m was considered. The spacing of frames - the main transverse systems - was assumed equal to 6.0 m. A case was considered in which the elements of the structure are unprotected from the influence of high temperature. The load carrying capacity, critical temperature and time required to reach the crit- ical temperature were analysed for column cross sections. The calculations were performed using Autodesk’s Robot Structural Analysis 2024 computer software. In the case of HEB-type profiles, the time required to reach the critical temperature at which the cross-section of the element loses its compressive capacity is significantly greater compared to that of IPE-type profiles. This is (as above) a recommendation for the use of solid elements, with low wall slenderness, for structures significantly exposed to fire and high temperatures